Pengaruh audit tenure, reputasi auditor, komite audit dan fee audit terhadap kualitas audit (studi empiris pada perusahaan yang terdaftar di indeks Kompas100 pada BEI Tahun 2012-2016) - Rizaldi, Sendy; Rahayu, Sri; Tiswiyanti, Wiwik (Jurnal Paradigma Ekonomika, 2022)
This study examines the influence of audit tenure, auditors' reputation, audit committees, and audit fees on audit quality. Audit quality uses current proxy accruals; while the term is measured by counting the year in which the same auditors have made an engagement with the auditee, the reputation of the auditor is measured by a dummy variable using the big four and non-big four groups of auditors, the audit committee is measured by the percentage amount of the audit committee comparing to the number of commissioners and audit fee measured by professional fees account on the financial statement. The population in this study consists of listed go public firm KOMPAS100 index on Indonesia Stock Exchange in the year 2012-2016. The sampling method used is purposive sampling. The sample's total is 135 from 27 firms over five years of research in this research—multiple regression analysis used to be the analysis technique. The empirical result of this study shows that audit tenure and reputation of the auditor had not significantly influenced audit quality. Meanwhile, the audit committee and audit fee variable positively affect the audit quality.